1993
DOI: 10.2737/pnw-rp-469
|View full text |Cite
|
Sign up to set email alerts
|

New Lepidoptera records for the Blue Mountains of eastern Oregon.

Abstract: Grimble, David G.; Beckwith, Roy C.; Hammond, Paul C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Other moth diversity studies carried out in various parts of North America recorded all of the species we found except N. rubrifrontaria. These other studies took place in diverse forested sites including balsam fir-red maple forests of New Brunswick (Thomas, 1996), mixed oak forests of West Virginia (Butler and Kondo, 1991), and riparian zones within coniferous forests of Oregon (Grimble et al, 1992). Thus, it seems unlikely that these moth species are burn specialists, except for N. rubrifrontaria.…”
Section: Discussionmentioning
confidence: 96%
“…Other moth diversity studies carried out in various parts of North America recorded all of the species we found except N. rubrifrontaria. These other studies took place in diverse forested sites including balsam fir-red maple forests of New Brunswick (Thomas, 1996), mixed oak forests of West Virginia (Butler and Kondo, 1991), and riparian zones within coniferous forests of Oregon (Grimble et al, 1992). Thus, it seems unlikely that these moth species are burn specialists, except for N. rubrifrontaria.…”
Section: Discussionmentioning
confidence: 96%
“…Firstly, limited training and supervision is required for a technician or parataxonomist to collect insect specimens in the field, roughly separate them into morphospecies, prepare the specimens for museum deposition, and sample them for DNA analysis. Moreover, Grimble et al (1992) conducted a comparable inventory in the Pacific Northwest region and tallied 383 nocturnal moth species. UV light traps, pitfall traps, flight interception traps) are employed, and specimens are not sorted to morphospecies, the process becomes even further routine.…”
Section: Barcode Recovery and Successmentioning
confidence: 99%
“…Hypena humuli is primarily associated with hops (Humulus lupulus L.) (Rosales: Cannabaceae), but has also occasionally been found on stinging nettles (Urtica spp.) (Urticales: Urticaceae) (Grimble and Beckwith 1992). These are the only recorded host plants of hop looper.…”
Section: Introductionmentioning
confidence: 98%